Immunogenicity and safety in pigs of PHH-1V, a SARS-CoV-2 RBD fusion heterodimer vaccine candidate - Moros, Alexandra; Prenafeta, Antoni; Barreiro, Antonio; Perozo, Eva; Fernández, Alex; Cañete, Manuel; González, Luis; Garriga, Carme; Pradenas, Edwards; Marfil, Silvia; Blanco, Julià; Cebollada Rica, Paula; et al. (Vaccine, 2023)
The continuing high global incidence of COVID-19 and the undervaccinated status of billions of persons strongly motivate the development of a new generation of efficacious vaccines. We have developed an adjuvanted vaccine candidate, PHH-1V, based on a protein comprising the receptor binding domain (RBD) of the Beta variant of SARS-CoV-2 fused in tandem with the equivalent domain of the Alpha variant, with its immunogenicity, safety and efficacy previously demonstrated in mouse models. In the present study, we immunized pigs with different doses of PHH-1V in a prime-and-boost scheme showing PHH-1V to exhibit an excellent safety profile in pigs and to produce a solid RBD-specific humoral response with neutralising antibodies to 7 distinct SARS-CoV-2 variants of concern, with the induction of a significant IFNγ+ T-cell response. We conclude that PHH-1V is safe and elicits a robust immune response to SARS-CoV-2 in pigs, a large animal preclinical model.